(untitled) (MATEMATIKA, 2017)
This paper presents an efficient analytical solution for fuzzy fractional differential equations (FDEs) using homotopy analysis method. HAM is the generalization of various methods like homotopy perturbation method and Adomian decomposition method. The main advantage is its rapid convergence to the solution without using perturbation or restrictive assumptions. Illustrative numerical example are presented for the proposed method.